(untitled) (Annals of Medical Research, 2022)
Background: Diseases of the skin and subcutaneous tissues still cause mortality in some parts of the world. This research aimed to examine the relationship between diseases of the skin and subcutaneous tissue-related mortality as of ICD-10 and health expenditure on purchasing power parity from the World Bank Database. Material and Methods: “Domestic private health expenditure per capita, PPP (current international )” and “Domestic general government health expenditure per capita, PPP (current international )” were collected from the World Bank Country Data for each country in which skin and subcutaneous tissue-related mortality were reported in the World Health Organization (WHO) ICD-10 Mortality database for 1996 to 2017. Results: A total of 13 countries were reported for mortality. Male deaths related to skin and subcutaneous tissue in Oman, Sri Lanka, Azerbaijan, Turkmenistan, and Ukraine were higher than female deaths. In Seychelles, Brunei Darussalam, Syrian Arab Republic, Belarus, Kazakhstan, and Russian Federation, female deaths were higher than male deaths. The correlation direction was positive, showing that an increase in country codes in the WHO ICD-10 list causes an increase in deaths. Conclusion: Deaths resulting even from skin diseases with an extremely low mortality level have been reported. At this point, when gender is discriminated, it is seen that women and men differ significantly in skin diseases. For this reason, studies and field applications must be carried out to raise awareness about skin diseases in the male gender.